Literasi dan Pelatihan Dasar Akuntansi Masjid berbasis ISAK 35 bagi Pengurus Masjid di Kota Bengkulu - Lisa Martiah Nila Puspita; Halimatusyadiah Halimatusyadiah; Darman Usman (Jurnal Nusantara Mengabdi, 2022)
Purpose: The purpose of the activity is to explain the urgency of masjid financial reporting that meets reporting standards and introduce and provide basic training on the use of simple masjid financial bookkeeping applications using excel to masjid managers. Method: This activity is carried out using a lecture method and technical guidance related to preparing masjid financial reports using a simple application. At the end of the activity, there was a question and answer session between the participants and the presenter. Results: Besides understanding the urgency of financial reporting according to applicable standards, masjid administrators also know the operational technicalities of masjid bookkeeping applications that can be applied in masjids that are their responsibility. Conclusion: This activity can motivate masjid administrators to carry out masjid financial reporting according to applicable standards. In addition, participants can identify all assets owned by large masjids and their activities which will be reported through a simple application offered.